2014
DOI: 10.1080/02678292.2014.951884
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of imidazolium-based ionic liquid crystals bearing a cholesteryl mesogenic group

Abstract: 2014) Synthesis and characterisation of imidazolium-based ionic liquid crystals bearing a cholesteryl mesogenic group, Liquid Crystals, 41:12, 1843-1853, A series of cholesteryl-containing imidazolium chlorides and imidazolium tetrachloroaluminates were synthesised, and the chemical structure, liquid crystalline behaviour and ionic conductivity were characterised by several technical methods. Whereas the imidazolium chlorides show chiral smectic A (SmA*) phase on heating and cooling cycles, the imidazolium tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“… [175] The occurrence of the N phase seems to be strictly limited to a maximum chain length of 8 C‐atoms. Besides these examples a few other non‐conventional ILCs displaying N phases have been reported [176–179] …”
Section: Rare Ilc Phasesmentioning
confidence: 93%
“… [175] The occurrence of the N phase seems to be strictly limited to a maximum chain length of 8 C‐atoms. Besides these examples a few other non‐conventional ILCs displaying N phases have been reported [176–179] …”
Section: Rare Ilc Phasesmentioning
confidence: 93%
“…[4,5] The studies of these substances have intensified during the last years. For example, imidazolium-based ionic liquid crystals bearing a cholesteryl mesogenic group were synthesised and characterised [6], effects of chain branching and lateral fluorine substitution on mesomorphism of cholesteryl benzoates has been investigated [7], as well influence of chemical structure on the optical properties of new side-chain polymers containing cholesterol was identified. [8] Cholesterol-based dimeric liquid crystals have also been studied in terms of mesomorphic properties of their frustrated phases.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid crystals (ILCs) have become an attractive functional soft material that combine the characteristics of ionic liquid and liquid crystal to exhibit anisotropic structure organization over a range of temperature . It has been reported that the liquid‐crystalline behavior of ILCs depends on the nature of the cations and anions that the ILCs have .…”
Section: Introductionmentioning
confidence: 99%